Evaluation of the developmental toxicity of perfluorooctanesulfonate in the Anuran, Silurana tropicalis. Issue 2 (14th September 2018) - Fort, Douglas J.; Mathis, Michael B.; Guiney, Patrick D.; Weeks, John A.
Abstract: A 150‐day post‐metamorphosis (dpm) partial lifecycle study exposing Silurana tropicalis to <0.03 (control), 0.06, 0.13 0.25, 0.5 and 1.0 mg/L perfluorooctanesulfonate (PFOS) was conducted. A subset of specimens from the control and each treatment were evaluated at metamorphic completion. A significant increase in the median metamorphosis time was observed in the 1.0 mg/L PFOS treatment relative to the control. A modest increase in the occurrence, but not severity, of mild follicular hypertrophy was found in thyroid glands from organisms exposed to the 0.62 and 1.1 mg/L PFOS treatments. At 150 dpm, a concentration‐dependent increase in whole body PFOS residues was measured ranging from 29.6 to 163.5 mg/kg in the 0.05 and 1.1 mg/L PFOS treatments. Decreased body weight and snout‐vent length were noted in specimens exposed to 1.1 mg PFOS/L at the completion of metamorphosis. Body weight was reduced in the 1.1 mg/L PFOS concentration; however, snout‐vent length was not affected by PFOS exposure at 150 dpm. An increased proportion of phenotypic males were noted in the 0.62 and 1.1 mg/L PFOS treatments. Abnormal ovary development characterized by size asymmetry, necrosis and formation of excessive fibrous connective tissue was identified in females exposed to 0.29 and 1.1 mg PFOS/L. Asymmetrically misshaped testes were found at 1.1 mg/L PFOS. Results suggested that PFOS is capable of interfering with S. tropicalis growth before metamorphic completion and growth and gonad development during juvenile development. Abstract : A 150‐day post‐metamorphosis partial lifecycle study exposing Silurana tropicalis to <0.03 (control), 0.06, 0.13 0.25, 0.5 and 1.0 mg/L perfluorooctanesulfonate was conducted. A subset of specimens from the control and each treatment were evaluated at metamorphic completion for: survival, rate of metamorphosis, body weight, snout‐to‐vent length and thyroid histopathology. Results suggested that perfluorooctanesulfonate is capable of interfering with S. tropicalis growth before metamorphic completion and growth and gonad development during juvenile development.